Radiation exposure during different percutaneous renal puncture techniques: A YAU endourology & urolithiasis study - ŞENER, TARIK EMRE; TANIDIR, YILÖREN; KÜTÜKOĞLU, MEHMET UMUT; DÖRÜCÜ, DOĞANCAN (My University, 2023)
PURPOSE: Radiation exposure is affected by C-arm fluoroscopy device positioning during percutaneous renal puncture. Our aim was to compare the exposure of surgeon\"s lens, hand and chest with a fluoroscopy protocol replicated in different C-arm positions. MATERIALS AND METHODS: A standardized fluoroscopy protocol was created using water-equivalent solid phantoms to replicate a surgeon and patient. 111 mGy radiation (360 s) was applied in standard fluoroscopy mode (91 kVp, 2.7 mA/mAs). Dosimeters were placed on lens, chest and hand of surgeon and patient phantom models. 7 different C-arm positions were created: 0°, mediolateral (ML) +90°, ML -90°, ML +30°, ML -15°, craniocaudal (CC) +30°, CC +15°. Measurements were evaluated separately for different positions. RESULTS: The highest radiation exposure was measured on patient dosimeter (2.97 mSv). The highest exposure on surgeon was recorded on finger dosimeter in all C-arm positions; highest dose was recorded in ML +90° position (2.88 mSv). In finger dosimeters, lowest exposure was recorded in 0° position (0.51 mSv). The lowest exposure of all positions was measured in chest dosimeter in ML -90° position (0.24 mSv). CONCLUSIONS: In positions where X-ray generator of the C-arm was facing towards the surgeon, radiation exposure measured in all dosimeters was higher compared to positions where the generator was facing away. The hand radiation exposure in all positions was higher than chest and lens. Special care must be taken to avoid facing the X-ray generator tube and hands should be as well-protected as chest and eyes with special protective gear.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; Percutaneous nephrolithotomy; Radiation exposure; Percutaneous nephrolithotomy; Radiation exposure